2002
DOI: 10.1021/es025764o
|View full text |Cite
|
Sign up to set email alerts
|

EXAFS and XANES Studies of Retention of Copper and Lead by a Lignocellulosic Biomaterial

Abstract: Lignocellulosic substrate (LS), which is a low cost biomaterial, has a strong complexing ability and can be used in the treatment of wastewaters as biosorbentto remove heavy metals. The speciation of copper and lead to this biomaterial has been studied by X-ray absorption spectroscopy. The copper(II) has a 6-coordinate structure with four oxygen atoms in the equatorial plane at 1.95 A and two in axial position at 2.35 A. In the case of lead a particularly low coordination number of about 3 has been obtained. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 37 publications
8
27
0
1
Order By: Relevance
“…The coordination number for root samples was particularly low compared to that of Pb(CH 3 COO) 2 Á3H 2 O because of the high structure disorder of the Pb coordination shells in root samples. Similar observations for Pb-O coordination have been reported for organic macromolecules such as humic acids, fulvic acids or salicylate in soils (e.g., Manceau et al 1996), for lichen cells exudates such as oxalate and parietinic acid (Sarret et al 1998), and for lignocellulosic biomaterial (Dupont et al 2002).…”
Section: Discussionsupporting
confidence: 84%
“…The coordination number for root samples was particularly low compared to that of Pb(CH 3 COO) 2 Á3H 2 O because of the high structure disorder of the Pb coordination shells in root samples. Similar observations for Pb-O coordination have been reported for organic macromolecules such as humic acids, fulvic acids or salicylate in soils (e.g., Manceau et al 1996), for lichen cells exudates such as oxalate and parietinic acid (Sarret et al 1998), and for lignocellulosic biomaterial (Dupont et al 2002).…”
Section: Discussionsupporting
confidence: 84%
“…6a, the fitting of this peak leads to 1.8 oxygen atoms at 2.37 Å for peat and 1.8 oxygen atoms at 2.39 Å for soil (Table 4). This result is similar to lead sorption studies reported by Dupont et al (2002) and Rouff et al (2004). As expected, the coordination number is particularly low because of high structural disorder of Pb coordination shell.…”
Section: X-ray Absorption Measurementssupporting
confidence: 91%
“…The fitting of this peak leads to 1.8 oxygen atoms at 2.38Å for Pb 2+ -MWCNTs-O(7.58%) and 1.8 oxygen atoms at 2.37Å for Pb 2+ -MWCNTs-O(2.66%). These results are similar to that of Dupont et al [43]. The coordination number was particularly low as expected because of the highly structural disorder of Pb coordination shells.…”
Section: Xas Analysissupporting
confidence: 92%